Earthquake site response analyses for soil conditions of several cities in Malaysia / Nasim Sarrafi Aghdam - Nasim Sarrafi, Aghdam (2018)
throughout a large earthquake may damage or cause failure of engineered constructions. Southeast Asia is an area of mutable seismic threat, fluctuating from high seismic threat related to the subduction procedure underneath the Indonesian and Philippine archipelagos to reasonably low risk of seismic behaviour through a large steady area surrounding Malaysian peninsula. Earthquake site response analysis has been the most important and challenging task in computerizing the earthquake time history. Earthquake ground response analysis is to predict ground motion on the surface, to develop the seismic microzonation maps and also design spectral response. An Earthquake ground response analysis contains several steps in order to achieve the main result which is the response spectra. The objectives of this study are to develop a site response program code considering the local soil dynamics and the Newmark method. The result obtained from this new program code is used to prepare seismic microzonation maps for four cities in Malaysia. The new maps are compared with the available ones in order to understand the effect of parameter variations. The Input data for the calculation include soil data, which is gained from the NSPT test, and the time history of the bedrock. These input data are computed with numerical methods such as; the dimensionality method of the space, calculation of Fast Fourier Transform (FFT) and Newmark method for computing the response spectra. The dimensionality of the space have been chosen for this research is one dimensional method. In order to gain the Amplification ratio of the ground surface motion the FFT is calculated. The numerical methods presenting the calculation of the time history of bedrock movement and conversion of the outcomes in to the response spectra are the main parts of the analysis. Based on the behaviour of the soil during the earthquake, programs are divided in three different aspects: linear, equivalent linear and also nonlinear. The nonlinear method, however, provides a better and more exact spectral ordinates. Hence, it is our main focus and the numerical methods based on the nonlinearity behaviour of soil such as Newmark method is considered in this study. This study has produced a new programming code for the nonlinear response analysis. The soil data collected from the different boreholes in 4 cities in Malaysia; Kuala Lumpur, Melaka, Penang and Johor Bahru, are used as an input data in the new program code. The results are compared with the available programs such as NERA, which concludes that using different soil dynamic properties and numerical methods in the new program code produced different results. The Amplification ratio values are applied in order to plot the seismic microzonation maps for mentioned cities. The comparison of maps with the available ones shows that the peak amplification factor in Kuala Lumpur is increased about 70%, for Penang and Melaka there is an escalation of 86%, while for Johor Bahru the growth is 18%.